CaFe2O4 oxygen carrier characterization during the partial oxidation of coal in the chemical looping gasification application. (15th August 2018) - Miller, Duane D.; Siriwardane, Ranjani
Graphical abstract: Highlights: Coal CLG with Ca ferrite evaluated using DFT/Raman spectroscopy/XRD. Oxygen ion diffusion-controlled regime occurred at the Fe octahedral sites. Ca functions to control O 2− movement and rate of carbon oxidation in coal char. Removal of O 2− from FeOCa occurs only during deep reduction of CaFe2 O4 . Abstract: The calcium ferrite (CaFe2 O4 ) oxygen carrier characterization during chemical looping coal gasification was conducted using X-ray diffraction and Raman spectroscopic analysis. Density functional theory (DFT) analysis and experimental data were used to elucidate the mechanism for the selective oxidation of coal char. The Raman spectroscopic analyses indicated that the initial reduction of CaFe2 O4 were at the Fe(8) O6 and Fe(7) O6 octahedral sites which are related to the morphological changes at the [4 0 0] and [2 1 2] crystal planes. After the initial reduction, the Raman spectroscopic data indicated the remaining oxygen from Fe-O sites containing Ca (e.g. FeOCa) participated in the reduction reaction. Deep reduction of the CaFe2 O4 led to the removal of oxygen from the FeOCa bonds, indicated by the decrease in Raman intensities of the corresponding species, and the appearance of the CaO and Fe 0 . The oxygen ion diffusion controlling regime was due to the oxygen transfer occurring at the Fe octahedral sites. These results indicated calcium functions to control both the movement of oxygen ions through the solid and the rate of carbon oxidation in coal char leading to the selective oxidation to produce CO, the desirable product of the chemical looping gasification application.